Political Options and Economic Prospects Within the Eastern Partnership - Ioana Sandu; Gabriela Dragan (CES Working Papers, 2016)
Recent changes in the security environment of Eastern Europe and the South Caucasus have been reshaping the strategies of the six small countries in the proximity of both the EU and Russia. Their attempts to take upon themselves their Soviet heritage and their sensitive geographical position were reflected by a mix of East-West orientations. Some of them chose to create stronger economic bonds with the EU members while others decided to anticipate Russian discontent in separatist areas they shelter and became members of the EEU. Regardless of their option, the Eastern Partnership members embarked? on a long road of political, social and economic changes, so that their stability and growth would become pillars of a stronger role on the regional and international arena in the future. The EU, in turn, has been supporting its partners to the East according to their level of commitment to reform and approximation, although the economic benefits of this relation are imperceptible.
Keywords: D72; D74; F13; F15; F51; N44; 330; Eastern Partnership; Association Agreements; frozen conflicts; conditionality; trade; approximation